Combination of chemotherapy and Au-nanoparticle photothermy in the visible light to tackle doxorubicin resistance in cancer cells - Pedrosa, Pedro (2019)
This work was supported by the Unidade de Ciencias Biomoleculares Aplicadas - UCIBIO which is financed by national funds from FCT/MEC (UID/Multi/04378/2013; UID/QUI/00100/2013) and co-financed by the ERDF under the PT2020 Partnership Agreement (POCI-01-0145-FEDER-007728); PP for PD/BD/105734/2014; RM for SFRH/BD/132163/2017. I. Coutinho for access to laser and P. Martins for initial induction of HCT116 DOXR.